Strategic planning for land use in Iraqi cities city Hit - Thaer Sh. Mahmood, Dr. (Anbar Journal of Engineering Sciences, 2016)
The role of strategic planning is particularly important in the development of trends graphic appropriate in the distribution of land uses for the city according to their importance and role in the development of the city. From this standpoint the idea of search to give the application of an analytical about how to adopt him graphical to insert the style of strategic planning and steps concatenated to give the relative importance of the distribution of applications and their role in the city's development in the future. two methods have been used in research assays are the factor analysis for the purpose of diagnosis and urban style quartet analysis SWOT developer + AHP for the purpose of determining the development priorities of the city and graphic orientation. Search concluded the conclusions and recommendations of the group serve the decision-makers and planners note that the study area to a city in Anbar province, Iraq (HIT) as a case study.